The role of pain, upper limb functioning and radiological changes in patients with thumb carpometacarpal osteoarthritis: a cross-sectional study - M. Paoletta; A. Moretti; S. Liguori; L. Giordano; A. Maucione; F. Tomaino; G. Iolascon (Verduci Editore, 2022)
OBJECTIVE: The aim of this study was to evaluate the characteristics of pain and its impact on upper limb functioning in patients with trapeziometacarpal osteoarthritis (TMC OA) and their relationship with site-specific radiological findings. PATIENTS AND METHODS: We performed a retrospective observational study including patients affected by TMC OA, according to the European League Against Rheumatism (EULAR) recommendations and graded with Eaton-Glickel classification. We excluded men and women under 50 years, patients with other hand disorders, and hand injuries in the last 24 months and previous hand surgery. Strength, pain, and disability of the upper limb were assessed in all patients with handheld Jamar dynamometer, Numeric Rating Scale (NRS) and disability by the Quick DASH (Disabilities of the Arm, Shoulder and Hand) scale, respectively. We divided our cohort in two groups according to Eaton-Glickel classification. First group included stage 1 and 2, whereas the second group included 3 and 4 stage. RESULTS: Our results demonstrated that patients with TMC OA have a significant reduction of strength and function of upper limb, and moderate-severe pain. However, the comparison according to all the outcome measures did not demonstrate significant difference between groups. CONCLUSIONS: Our findings demonstrated that the severity of radiological stage assessed with Eaton-Glickel classification is not correlated with the magnitude of symptoms, especially pain and upper limb function.